The Evaluation Of Local Expenditure And Revenue Performance In Implementing Local Autonomy On Kendari Local Government - Fahmi Sahlan; Sriayu Pracita (Jurnal Penelitian Ekonomi dan Akuntansi (JPENSI), 2023)
The purpose of this study was to analyze the regional financial reports of Kendari City using the ratios of effectiveness, efficiency, independence, harmony, and growth. This type of research was descriptive quantitative by using data sourced from Kendari City budget realization reports for the period 2016 – 2020. The results of this study indicate that the average effectiveness ratio of the Kendari City local government from 2016 to 2020 had ineffective criteria, which value was below 100 %, which equaled 59.95%. The average regional efficiency ratio for Kendari City from 2016 to 2020 was efficient at 98.78%. The average independence ratio for Kendari City from 2016 to 2020 in financing development and services to the community was 19.79% with the criteria being very low and the pattern of relationship being instructive. The average compatibility ratio for Kendari City in 2016-2020 in meeting the operation expenditure needs was 68.41%, while in meeting the capital expenditure needs was 30.58%. The average financial growth for Kendari City from 2016 to 2020 in realizing the revenue budget was -1.86% with a negative value, in the realization of the locally-generated revenue budget was 6.96% with a positive value, in realizing the regional expenditure budget was -3. 34% with a negative value, in realizing the operational expenditure budget was -2.31% with a negative value, and in the realization of the capital expenditure budget was -7.15% with a negative value.